(untitled) (PANGEEA, 2025)
Karst phenomena present in perimeter “Măgura Geomalului”. Mount Magura Geomalului is a part of Trascău Mountains, the southeast branch of the Apuseni Mountains. The mountain is composed of limestone and contains a large number of karst phenomena: ditches, potholes, caves. Few of them are researched and studied. These and attractive landscape provides area an important tourism potential, amplified by easy access, on paved roads, almost to the caves.